2005
DOI: 10.1111/j.1365-2583.2004.00527.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles among immature and adult reproductive castes of the termite Reticulitermes flavipes

Abstract: Array-based genomic studies were conducted with the goal of identifying immature (i.e. nymph) and adult reproductive caste-biased gene expression in the termite Reticulitermes flavipes. Using cDNA macro-arrays, we identified thirty-four nymph-biased genes falling into eight ontogenic categories. Based on gene expression profiles among diverse castes and developmental stages (determined by quantitative PCR), several important trends emerged. These findings highlight the importance of several developmental and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
95
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 43 publications
6
95
1
Order By: Relevance
“…19). One of these duplications is closely related to Neofem3, a reproductive-specific gene in three other termite species (Cryptotermes secundus, C. cynocephalus and Reticulitermes flavipes) [35][36][37][38] . Three of the four Vg genes, including the recent duplications, were significantly overexpressed in reproducing queens (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…19). One of these duplications is closely related to Neofem3, a reproductive-specific gene in three other termite species (Cryptotermes secundus, C. cynocephalus and Reticulitermes flavipes) [35][36][37][38] . Three of the four Vg genes, including the recent duplications, were significantly overexpressed in reproducing queens (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to knowing their identity, hemolymph-soluble hexamerin protein forms were found to increase in abundance during JH-induced soldier caste differentiation (Scharf et al, 2005a). From nymph and presoldier array screens, expressed sequence tags representing the two hexamerins were identified and, subsequently, fulllength cDNA sequences were obtained (Scharf et al, 2005b;Zhou et al, 2006b). The protein sequences deduced from the full-length cDNAs revealed that the Hex-1 protein has a unique hydrophobic tail with a putative JH-binding prenylation site and that the Hex-2 protein has a unique hydrophilic insertion with unknown function.…”
Section: Hexamerin-based Regulationmentioning
confidence: 99%
“…Several tools and resources have become available in recent years to study the molecular basis of termite caste differentiation (5,6,10,11,18). Using these tools, we previously identified two JH-responsive and morphogenesis-associated hexamerin genes that are referred to as Hex-1 and Hex-2 (6,11).…”
mentioning
confidence: 99%
“…Termite caste differentiation is a postembryonic developmental process that is the result of differential gene expression (4)(5)(6)(7). Lower termites such as the Reticulitermes undergo a caste differentiation process that is truly unique among the social insects (see Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation